CYTOTOXIC ACTIVITY OF A MEDICINAL MANGROVE PLANT CERIOPS DECANDRA (GRIFF.) DING HOU LEAVES ON HUMAN BREAST ADENOCARCINOMA CELL LINE MCF-7 - S, Sukasini; M, Bhargav Iyer (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Ceriops decandra (Griff.) Ding Hou (Rhizophoraceae) is an evergreen mangrove tree widely used in folklore medicine for the treatment of several diseases. Concerning the presence of anticancer molecule in C. decandra, the present investigation was carried out to study the preliminary phytochemical screening, in vitro cytotoxic effect, and apoptotic induction of methanol extract of C. decandra. Methods: The preliminary phytochemical investigations were done using standard methods. Cytotoxic activity was analyzed in terms of brine shrimp (Artemia salina Leach) lethality bioassay. MTT (3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide) assay was used to evaluate the cell viability and growth inhibition of MCF-7 (human breast adenocarcinoma) cells after treatment with different doses of C. decandra extract. Cell morphological changes induced by the extract were observed using phase contrast inverted microscope. Induction of apoptosis was determined by DNA fragmentation assay. Results: Phytochemical screening revealed the presence of various potent phytochemicals. In the brine shrimp lethality bioassay, the LC50 of the extract was found to be 12.5 Î¼g/mL, implying a promising cytotoxic effect. The MTT assay results showed increased inhibitory activity at a concentration-dependent manner and altered the cell morphology after exposure with C. decandra extract which exhibited typical apoptotic morphological changes. Furthermore, the characteristic DNA ladder pattern of C. decandra treated cells in agarose gel electrophoresis confirms the induction of apoptosis. Conclusion: The research revealed the cytotoxic effect of C. decandra on MCF-7 cells through its nature of induction of apoptosis.